Теща Франкенштейна: [роман] / Наталья Александрова - Александрова Наталья Николаевна (Смешные детективы, 2009)
Экземпляры: (20170505) / Инвентарный номер: 34415 / Цена: 109.00 / Сис.шифр: Р2 / Авт.знак: А 465 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6